Passive Knee Exoskeleton Increases Vertical Jump Height - Coral Ben-David; Barak Ostraich; Raziel Riemer (IEEE, 2022)
Most exoskeletons are designed to reduce the metabolic costs of performing aerobic tasks such as walking, running, and hopping. This study presents an exoskeleton that boosts vertical jumping—a fast, short movement during which the muscles are exerted at peak capacity. It was hypothesized that a passive exoskeleton would increase vertical jump height without requiring external energy input. The device comprises springs that work in parallel with the muscles of the quadriceps femoris. The springs store mechanical energy during knee flexion (the negative work phase) and release that energy during the subsequent knee extension (the positive work phase), augmenting the muscles. Ten healthy participants were evaluated in two experimental sessions. In the first session, the participants jumped without receiving instructions on how to use the exoskeleton, and the results showed no difference in jump height when jumping with the exoskeleton or jumping without it. In the second session, the participants were instructed to achieve deeper initial squat heights at the start of the jump. This resulted in a 6.4% increase in average jump height compared to jumping without the exoskeleton (each participant performed five jumps for each the two conditions). This is the first time that a passive exoskeleton has been shown to improve the height of a vertical jump from a dead stop.